Penentuan Awal dan Durasi Musim Kemarau Menggunakan Fungsi Polynomial dengan Aplikasi Visual Basic for Applications (VBA) - Fadli Irsyad; Satyanto Krido Saptomo; Budi Indra Setiawan (PERHIMPI (Indonesian Association of Agricultural Meteorology), 2014)
Forecasting the occurrence of the onset of dry season and its length is important in determining the availability of water for irrigation, domestic and industrial uses. The length of dry season is used for reference in calculating water demand. Prediction of drought can be studied based on the rainfall patterns that have occurred. This is possible because there is a tendency that the rain will repeat a certain pattern at a certain time. The purpose of this study was to predict the onset of dry and rainy seasons as well as their length. Determination of the onset of dry season and its length was conducted using polynomial function of the cumulative amount of rain every single day based on the rain data. The research was conducted using rainfall data from Climate Station III in Serang from 1989 to 2010. The sum of daily rainfall could form a polynomial function. If the magnitude of daily rainfall in a certain period of time is less than the slope of the cumulative annual rainfall, then at that time the dry season is occurred. Determination of the dry season peak can be done by finding the maximum (extreme) point from the polynomial function by getting the second derivative which value is close or equal to zero. In average, the dry season occurred in Serang city started on the 132nd until 300th day. Deviation value for the onset of dry and rainy seasons were 23 and 38 days, respectively, with an average of length of 168 days. The average of R2 value for polynomial function was 0.9937.